Transient Reduction of FMD-Response and L-Arginine Accompanied by Increased Levels of E-Selectin, VCAM, and ICAM after Prolonged Strenuous Exercise - Christoffer Nyborg; Helene Støle Melsom; Martin Bonnevie-Svendsen; Jørgen Melau; Ingebjørg Seljeflot; Jonny Hisdal (MDPI AG, 2021)
We assessed endothelial function by flow-mediated dilatation (FMD), levels of the NO-precursor L-arginine, and markers of endothelial inflammation before, at the finish line, and one week after the Norseman Xtreme triathlon. The race is an Ironman distance triathlon with a total elevation of 5200 m. Nine male participants were included. They completed the race in 14.5 (13.4-15.3) h. FMD was significantly reduced to 3.1 (2.1-5.0)% dilatation compared to 8.7 (8.2-9.3)% dilatation before the race (p < 0.05) and was normalized one week after the race. L-arginine showed significantly reduced levels at the finish line (p < 0.05) but was normalized one week after the race. Markers of endothelial inflammation E-Selectin, VCAM-1, and ICAM-1 all showed a pattern with increased values at the finish line compared to before the race (all p < 0.05), with normalization one week after the race. In conclusion, we found acutely reduced FMD with reduced L-arginine levels and increased E-Selectin, VCAM-1, and ICAM-1 immediately after the Norseman Xtreme triathlon. Our findings indicate a transient reduced endothelial function, measured by the FMD-response, after prolonged strenuous exercise that could be explained by reduced NO-precursor L-arginine levels and increased endothelial inflammation.